Effectiveness of Resiliency Components Education on Reduction of Addiction Vulnerability Level and Changing Attitude Towards Substance Use in High School Students - Hamidreza Zarrin Kelk (Drug Control Headquarters, Research and Education Office, 2009)
Introduction: The aim of this study was to examine the effectiveness of resiliency components education program on reduction of addiction vulnerability level and changing students' attitude towards substance use. Method: The research method was an experimental design with pretest - post test and control group. The sample was 50 students who were selected by clustering random sampling of first year students of Terhan (countryside namely: Karaj, Eslam Shahr, Bomehen, Rodehen, Shahr-e-Rei). The selected sample assigned to experimental (25 students) and control (25 students) groups randomly. The research tools were scale of attitude towards substance use and scale of addiction vulnerability and the data was analyzed by ANCOVA and Pearson correlation. Results: The result showed significant difference attitude towards substance use total scores and addiction vulnerability subscales between experiential and control group. Conclusion: The result of the study indicates effectiveness of resiliency components education program in changing attitude of students towards substance use and reduction of addiction ability level is compatible with previous studies. Therefore, results confirm the efficiency of resiliency components education program in prevention of substance abuse.